Refractive index dispersion and analysis of the optical constants of an ionomer thin film - Yakuphanoğlu, Fahrettin; Erten, H (Technical Univ Wroclaw, 2005)
The basic optical properties and optical constants of the ionomer thin film have been investigated by means of transmittance and reflectance spectra. The real (n) and imaginary (k) parts of the complex refractive index and dielectric constant of the thin film were determined. The oscillator energy E-o, dispersion energy E-d and other parameters have been determined by the Wemple-DiDomenico method. The optical band gap E-g was determined and the optical absorption spectra show that the absorption mechanism is a direct transition. The most significant result of the present study is to determine optical constants and optical band gap of the thin film.
Keywords: polymer; thin film; optical constants; optical band gap